Clinician's perspective on the diagnosis of primary cutaneous B-cell lymphoma - Christian Ciolfi; Jacopo Tartaglia; Alvise Sernicola; Mauro Alaibac (PAGEPress Publications, 2023)
Primary cutaneous B-cell lymphomas (PCBCLs) account for 25% of all cutaneous lymphomas: the main subtypes within this group are primary cutaneous follicle center lymphoma (PCFCL), primary cutaneous marginal zone B-cell lymphoma (PCMZL), and primary cutaneous diffuse large B-cell lymphoma, leg type (PCDLBCL, LT). Biopsy with histological examination and immunohistochemistry is the gold standard for the diagnosis of PCBCLs. A clinically oriented approach to PCBCLs classifies these entities according to their clinical behavior into indolent or intermediate to aggressive subtypes. While PCFCL and PCMZL are indolent diseases, PCDLBCL, LT has an aggressive course spreading to extracutaneous sites in approximately 45% of cases. Therefore, instrumental staging for extracutaneous disease is not performed following a diagnosis of PCMZL and PCFCL, while it is recommended for PCDLBCL, LT. Finally, dermatoscopy, under the guide of a strong clinical suspicion, may provide a novel diagnostic tool to enhance the clinical recognition of different subtypes of PCBCL.